Hepatic Anti-Oxidative Genes CAT and GPX4 Are Epigenetically Modulated by RORγ/NRF2 in Alphacoronavirus-Exposed Piglets - Haotian Gu; Yaya Liu; Yahui Zhao; Huan Qu; Yanhua Li; Abdelkareem A. Ahmed; Hao-Yu Liu; Ping Hu; Demin Cai (MDPI AG, 2023)
As a member of alpha-coronaviruses, PEDV could lead to severe diarrhea and dehydration in newborn piglets. Given that lipid peroxides in the liver are key mediators of cell proliferation and death, the role and regulation of endogenous lipid peroxide metabolism in response to coronavirus infection need to be illuminated. The enzymatic activities of SOD, CAT, mitochondrial complex-I, complex-III, and complex-V, along with the glutathione and ATP contents, were significantly decreased in the liver of PEDV piglets. In contrast, the lipid peroxidation biomarkers, malondialdehyde, and ROS were markedly elevated. Moreover, we found that the peroxisome metabolism was inhibited by the PEDV infection using transcriptome analysis. These down-regulated anti-oxidative genes, including GPX4, CAT, SOD1, SOD2, GCLC, and SLC7A11, were further validated by qRT-PCR and immunoblotting. Because the nuclear receptor RORγ-driven MVA pathway is critical for LPO, we provided new evidence that RORγ also controlled the genes CAT and GPX4 involved in peroxisome metabolism in the PEDV piglets. We found that RORγ directly binds to these two genes using ChIP-seq and ChIP-qPCR analysis, where PEDV strongly repressed the binding enrichments. The occupancies of histone active marks such as H3K9/27ac and H3K4me1/2, together with active co-factor p300 and polymerase II at the locus of CAT and GPX4, were significantly decreased. Importantly, PEDV infection disrupted the physical association between RORγ and NRF2, facilitating the down-regulation of the CAT and GPX4 genes at the transcriptional levels. RORγ is a potential factor in modulating the CAT and GPX4 gene expressions in the liver of PEDV piglets by interacting with NRF2 and histone modifications.